تصور مقترح لمنهج القيم الأخلاقية وفق حاجات طلاب المرحلة الابتدائية - عتيق، عبدالمحسن بن مبارك (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The purpose of this study is to propose a moral-values models in accordance to the needs of primary school students (higher grades). The samples of this study are 357 primary school teachers at Al-Ihsa Governorate, Kingdom of Saudi Arabia. Two sets of questionnaires were used in the study. The first questionnaire was to find out the moral values needed by student. The second questionnaire is to determine the standardized specifications of the elements of the methodology of moral values curriculum which has been built upon the basis of the proposed design. A number of statistical methods were utilized to analyze data: frequencies, percentages, mean and standard deviation. The most prominent the results of this study were: Dissimilar between researchers about studying moral values which has been needed by students in the upper grades at the primary level; Specifying the distribution of sixteen frequent moral values in each class of the upper grades to take into account the principle of relay/succession in teaching (either two or three classes might be included); The identification of standardized specifications that must be achieved in curriculum elements (objectives, content, teaching techniques, educational activities, learning aids, educational evaluation). The suggested proposal was based on those standardized specifications. The most prominent recommendations of this study were: Adding a separate curricula (for Moral Education) in the Kingdom of Saudi Arabia starts from the first grade and extends to all stages; Adopting of the suggested proposal to the moral values of the curricula throughout the findings of this study; Highlighting the importance of developing all moral values needed by the students as suggested by the study, through the inclusion of various courses and employing them in classroom or extra-curricular activities.